Athletic and academic motivations of student-athletes in martial arts sports during the COVID-19 pandemic - Rodriguez, Dianne G.
The qualitative study explores the experiences of student-athletes in martial arts sports during the COVID-19 pandemic, focusing on their motivation and how they navigated their dual responsibilities as students and athletes. The research aims to understand how these student-athletes made sense of their experiences and identify the best ways to support their needs during times of uncertainty. The research employs a descriptive qualitative design, utilizing in-depth interviews to capture the experiences of six student-athletes in martial arts during the pandemic. The findings reveal significant challenges and emphasize the remarkable motivations of student-athletes and their ability to maintain their dual roles. The findings highlight the importance of goal orientation, attention regulation, and social support in maintaining motivation. The study concludes that understanding the experiences and needs of student-athletes in martial arts sports is crucial for developing effective support systems that promote their well-being and academic success, especially during challenging times. The study also proposes an integrative support framework to address the holistic needs of student-athletes in martial arts sports. This framework emphasizes the importance of personalized support systems that cater to the academic, athletic, and mental health concerns faced by student-athletes.